A Study of Real-time Detection Methods for Solar Radio Burst Identification - YongLin Yu; ChengLong Qiao; Shuo Xu; QinZheng Li; YanRui Su; HongQiang Song; FaBao Yan (The Astrophysical Journal Supplement Series)
Solar flares, coronal mass ejections, and other solar radio burst phenomena release substantial amounts of solar radiation energy, resulting in adverse space weather conditions and posing significant hazards in space. Spectrum analysis conducted manually or with traditional image processing algorithms is limited by low efficiency and accuracy. This paper investigates solar radio burst detection methods and their applications. Five solar radio burst detection methods—Continuous-3 σ , Sum Flux-3 σ , Continuous Slope, Sum Flux Slope, and Sum Flux Continuous-3 σ —are developed and validated using data from the Japanese NoRP and the Australian Learmonth Solar Radio Observatory. The results show that all five methods can detect solar radio bursts to some degree. Considering the combined metrics of success rate, false detection rate, and real-time performance, the Sum Flux Continuous-3 σ method is deemed the optimal method among the five. Additionally, the Sum Flux Slope method, which is not reliant on historical data, demonstrates superior universality. Finally, we implement the Sum Flux Slope method on a 39.5–40 GHz two-element interferometer, achieving real-time solar radio burst detection in the upper computer software. The method also includes functionalities for email alerts, burst information recording, and control parameter adjustment, confirming its effectiveness and practicality. Test results demonstrate the method’s effectiveness in real-time solar radio burst detection.